A historical analysis of home advantage on medal performance among Olympic hosting nations - Zhang, M.; Boukas, S.; Chen, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The existence of home advantage in sport is a well known and documented phenomenon. Apparently, such effects are present during the Olympic Games. Of the 17 countries having hosted the Olympic Games prior to Beijing, 14 countries have won their greatest percentage of total medals awarded while hosting the Games. The purpose of this research was to analyze the impact of home advantage on hosting nations` medal performance during the Games and in later Olympiads. Methods This qualitative research with a historical perspective compared the medal performances of 17 Olympic Games hosting nations prior, during, and after hosting the Games. Instead of comparing the number of medals, this study compared the nations` medals earned as a percentage of the total medal awarded. It is a more objective approach than simply comparing the number of medals due to the gradual increase in the size of the Games through the years. This study emphasized three particular Olympic Games: the Mexico City Games of 1968, the Seoul Games of 1988, and the Barcelona Games of 1992. The reason for this comparison is to analyze the benefits for these developing countries that are neither Group of 8 (G8) countries nor economically developed Anglo-Saxon countries by which the most Games were hosted.